(untitled) (Baghdad Science Journal, 2016)
A series of lanthanide metal (???) complexes have been prepared from the new azo ligand, 3-(1-methyl-2-benzimidazolylazo)-Tyrosine (MBT). The structural feature were confirmed on the basis of their elemental analysis, metal content, molar conductance, magnetic measurement, FTIR, 1 HNMR and UV-Vis spectra studies. The isolated complexes were found to have a mole ratio (1:2) (metal:ligand) stoichiometry with the general formula [Ln(MBT)2]Cl (Ln(???) = La, Ce, Pr, Nd, Sm, Eu and Gd). The chelates were found to have octahedral structures. The FTIR spectra shows that the ligand (MBT) is coordinated to lanthanide ions as a N, N, O-tridentate anion via benzimidazole nitrogen, azo nitrogen and oxygen of hydroxyl after deprotonation. Complexes formation in solution were performed after fixing the optimum pH, molar concentration and time. Beer’s low was obeyed over a range (7-9x10-5) with high molar absorptivity for all the prepared complexes solutions. Stability Constant and Gibbis free energy were also determined. The ligand (MBT) and its prepared complexes were screened invitro against two types of selected bacteria.